How technology shapes our experience - Płotka, Witold (Phainomena (Ljubljana), 2025)
The article aims to interpret Blaustein’s phenomenology of aesthetic experiences from the perspective of the philosophy of technology. In order to do this, I sketch some parallels between today’s inquiries into the nature of technology and Blaustein’s accounts of experiences of the cinemagoer or the phenomenon of listening to the radio. The study is divided into 5 sections. In section 1, I explore the question of why the framework of the philosophy of technology can be useful in reading Blaustein’s writings. Section 2 presents Blaustein’s two main research strategies, while analyzing the phenomenon of technology, i.e., the humanistic and phenomenological methods. Moreover, the question of the compatibility of both approaches is examined. Next, in section 3, different phenomena from the field of the aesthetics of media are analyzed, in order to show to what extent technology mediates one’s conscious experiences. Section 4 turns toward the question of the body and environment in technologically determined experiences. Finally, in section 5, the main elements of Blaustein’s philosophy of technology are examined.
Keywords: aesthetic experiences; embodiment; estetsko izkustvo; kvazi-prostor; Leopold Blaustein; quasispace; technological artefacts; tehnološki artefakti; utelešenje